Applications of simulation in micromachining: a literature review - Maia, Tânia Dálete Pires; Reis, Laura Teodora Miotto; Santos, Aline Gonçalves dos; Resende, André Alves de; Bachega, Stella Jacyszyn (Brazilian Journal of Production Engineering, 2026)
Micromachining has gained increasing importance due to the growing demand for micrometric-scale components. In this context, simulation emerges as an important tool, enabling detailed modeling and analysis of micrometric processes without the need for physical experimentation. This article aims to conduct a literature review on the application of simulation in micromachining, identifying the main variables analyzed and the software used. To achieve this objective, the topic was first delineated to identify gaps in the research field, and the search terms “micromachining” and “simulation” were defined. The data sources consulted were those indexed in SCOPUS. In the second phase, the method for selecting the articles was established, starting with a screening of abstracts and subsequently a full reading of the articles for final selection. A bibliometric analysis of the publications addressing the use of simulation in micromachining was also conducted. The information extracted from the studies included the materials investigated, the parameters used, and the variables controlled. In the final phase, the review was written and the conclusions were formulated. The results show that simulation is an important tool in micromachining, offering an in-depth understanding of the processes and enabling the optimization of various parameters.